Optimizing Employee Performance through Compensation and Work Motivation at PT Pos Indonesia (Persero) Medan - Tri Anatasya; Amril; Putri Mauliza (Outline Publisher, 2026)
Purpose: The purpose of this study was to determine the effect of compensation and work motivation on employee performance at PT. Pos Indonesia (Persero) Medan. Methods: Respondents in this study were employees of PT. Pos Indonesia (Persero) Medan with a population of 100 people and a sample of 50 people. The research sampling technique used the census method. The research method used was quantitative. The data collection technique used a questionnaire. Results: Based on the results of the study, there was an influence between the compensation variable on employee performance variables of t count = 7.014, there was an influence between the work motivation variable on employee performance variables of t count = 6.628, and there was an influence between the compensation variable, work motivation simultaneously on employee performance variables of F count = 49.839. Conclusions: The results indicate that compensation and work motivation significantly contribute to improving employee performance, both partially and simultaneously. Therefore, companies are encouraged to enhance compensation systems and strengthen employee motivation strategies in order to achieve optimal organizational performance. Originality/value: The originality of this study lies in its focus on examining the simultaneous role of compensation and work motivation in improving employee performance within the context of PT. Pos Indonesia (Persero) Medan, which provides empirical evidence for human resource management practices in the Indonesian postal service sector.